Walking on the grammaticalization path of the definite article functional main and side roads - Szczepaniak, Renata; Flick, Johanna (Studies in language variation, 2020)
"This volume focuses on the grammaticalization of the definite article in German. It contains eight empirically-based papers which examine individual stages of the grammaticalization path from its beginnings as a demonstrative to the definite article and beyond. Focusing on cognitive, pragmatic, semantic and syntactic factors, the contributions not only address the development from pragmatic to semantic definiteness, but also pertain to functional and formal changes starting as soon as the linguistic unit has acquired the function of marking semantic definiteness. Based on corpora spanning the entire history of the German language, from Old High German (750-1050) to present-day German, the analyses challenge the traditional linear model of grammaticalization and provide alternative pathways. What all the contributions have in common is the idea that the main grammaticalization path is accompanied or crossed by several side roads which lead to different destinations such as preposition-article-clitics, generic usages or onymic articles"--